The influence of circulating cholesterol and its components in middle-aged adults on cognitive function at mid- and later-life; a systematic review - Joyce, O. C.; McHugh, C.; Mockler, D.; Wilson, F.; Kelly, Á. M. (Frontiers in Aging, 2025)
IntroductionSeveral measures of cardiovascular health have been investigated as potential risk factors for development of cognitive decline in mid-to later-life, among them, circulating cholesterol. However, the efficacy of midlife interventions aimed at reducing blood cholesterol to mitigate the risk of cognitive decline is uncertain, with conflicting evidence reported from a range of longitudinal and cross-sectional studies. This review systematically investigates the connection between cholesterol measures in midlife and their impact on cognitive function in both mid- and later-life.MethodsElectronic databases were explored from their inception until December 2023. Studies that evaluated the relationship between cholesterol and its sub-components in midlife (40–65 years) and cognitive function in mid and/or later-life were included. Qualitative analysis was used to assess the associations between cholesterol and cognition according to cognitive domains (positive, negative, or neutral).Results106 studies were included. We found inconsistent reporting on the association between midlife cholesterol and its sub-components, and cognitive function in older age. Longitudinal cohort studies (75%) generally showed no significant link between midlife cholesterol metrics and later-life cognitive domains. Conversely, half of individual cohort studies (50%) reported negative associations with memory, executive function, global cognition, and psychomotor speed. Most studies (78.6%) found no clear relationship between midlife cholesterol metrics and cognitive function either at midlife or later life, irrespective of study design or quality.DiscussionOur review found no conclusive link between midlife cholesterol and cognitive function in mid- and later-life, contrasting with the recent inclusion of high-LDL cholesterol as a modifiable risk factor for dementia by the 2024 Lancet Commission, following its exclusion in 2020 due to lack of evidence. These conflicting reports highlight the need to continue to investigate the importance of cholesterol metrics at midlife on cognitive function throughout the lifespan. Meanwhile, efforts to manage the all of cognitive decline in mid- and later-life across the population should continue to focus on other modifiable variables.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021238293.